1999
DOI: 10.1161/01.hyp.33.5.1190
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol With or Without Progesterone and Ambulatory Blood Pressure in Postmenopausal Women

Abstract: Abstract-The purpose of this study was to determine whether transdermal estradiol and intravaginal progesterone given in doses to mimic the premenopausal state would lower blood pressure (BP) in postmenopausal women. Fifteen healthy postmenopausal women were studied in each of 3 conditions: on placebo, after 8 weeks of transdermal estradiol 0.2 mg twice per week, and again 2 weeks after addition of intravaginal progesterone 300 mg/d. Women were studied at each point after 2 days of 100 mmol/d sodium intake. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(107 citation statements)
references
References 29 publications
5
96
1
5
Order By: Relevance
“…Journal of Human Hypertension in agreement with the hypothesis that oestrogen deprivation, either at the onset of menstruation 27 or in non-substituted postmenopausal normotensive [23][24][25] or hypertensive 22 women, may increase blood pressure. Oestrogens change the loading conditions on the elastin or collagen fibres or alter the structure of the vessel wall.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Journal of Human Hypertension in agreement with the hypothesis that oestrogen deprivation, either at the onset of menstruation 27 or in non-substituted postmenopausal normotensive [23][24][25] or hypertensive 22 women, may increase blood pressure. Oestrogens change the loading conditions on the elastin or collagen fibres or alter the structure of the vessel wall.…”
Section: Discussionsupporting
confidence: 86%
“…18 Other studies are in keeping with our findings, but did not correct for the level of blood pressure [19][20][21] or reported that withdrawal of hormonal replacement therapy for 4 weeks resulted in a decrease of systemic arterial compliance and an increase in pulse wave velocity in the femoralisdorsalis pedis region, but not in the aorto-femoral territory. 21 Recent studies using ambulatory monitoring [22][23][24][25][26] or automated blood pressure self-measurement 27 are…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study used a double-blind, randomised, placebocontrolled design with adequate power to detect small changes in clinic and ambulatory blood pressure produced by different doses of a C21 progestogen administered in a cyclical regimen in doses spanning the usual clinical dose range combined with a fixed daily dose of oral oestrogen. The results of the current study are consistent with those of previous studies, including the PEPI study, which have found no change [2][3][4][5][6][7][8][9][10]12 or a reduction [24][25][26]29 in blood pressure associated with the addition of a progestogen to 'replacement' doses of oestrogen.…”
Section: Discussionsupporting
confidence: 91%
“…Collectively, previous studies have variably shown no change, 1-12 a decrease 1,2,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] or an increase 4,9,11,21,[30][31][32][33][34][35] in blood pressure with various combinations of HRT. Unfortunately, few of the previous studies have been designed to differentiate between the effects on blood pressure of the individual oestrogen ('natural', conjugated equine or semisynthetic) and progestogen (C21 or C19 derivatives administered as cyclical or continuous therapy) components of the regimen when these preparations have been administered in combination.…”
Section: Introductionmentioning
confidence: 99%